Combination of i‐Motif and G‐Quadruplex Structures within the Same Strand: Formation and Application1. Issue 30 (14th June 2013) - Zhou, Jun; Amrane, Samir; Korkut, Dursun Nizam; Bourdoncle, Anne; He, Hong‐Zhang; Ma, Dik‐Lung; Mergny, Jean‐Louis
<x xml:space="preserve">Abstract</x> Peaceful coexistence: A double quadruplex composed of an i‐motif and a G‐quadruplex was constructed within one oligonucleotide strand (see picture). The defined double‐quadruplex structure can serve as a NOTIF logic gate on the basis of the fluorescence of crystal violet.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>